Clinical outcomes related to molecular allergy diagnosis. Issue 3 (June 2019) - Melioli, Giovanni; Puggioni, Francesca; Racca, Francesca; Descalzi, Desideria; Canonica, Giorgio Walter; Heffler, Enrico
Abstract : Purpose of review: Aim of this review is the description of the medical conditions in which the support of molecular allergy diagnostics (MAD) has an impact on the clinical outcomes, such as laboratory diagnostics, prognosis, and therapy of allergic diseases. Recent findings: The review of the literature of the last 2 years generated a wide number of results on this topic. As expected, not all were obtained by the use of MAD, but, in general, a clear trend is evident. Summary: Within the large number of works available, laboratory allergy diagnostics seems to be the most frequently discussed topic, in particular considering the complexity of the biological environment where these assays are used. Some interesting news arrive from the prognostic potential of MAD, whereas for allergen immunotherapy, waiting for a well-conducted prospective randomized clinical study, data from retrospective studies still confirms the added values of MAD in the management of the allergic patients.